Approaches to Unmask Functioning of the Uncultured Microbial Majority From Extreme Habitats on the Seafloor - Böhnke, Stefanie; Perner, Mirjam (Frontiers in Microbiology, 2022)
Researchers have recognized the potential of enzymes and metabolic pathways hidden among the unseen majority of Earth’s microorganisms for decades now. Most of the microbes expected to colonize the seafloor and its subsurface are currently uncultured. Thus, their ability and contribution to element cycling remains enigmatic. Given that the seafloor covers 70% of our planet, this amounts to an uncalled potential of unrecognized metabolic properties and interconnections catalysed by this microbial dark matter. Consequently, a tremendous black box awaits discovery of novel enzymes, catalytic abilities, and metabolic properties in one of the largest habitats on Earth. This Mini Review summarizes the current knowledge of cultivation-dependent and -independent techniques applied to seafloor habitats to unravel the role of the microbial dark matter. It highlights that microbiological and biogeochemical data from in situ experiments collected in appropriate spatial and temporal proximity combined with molecular tools, offer great potential to provide a more complete understanding of seafloor habitat biology and uses hydrothermal vents as an example case.